A Parsimonious Model of Divine Simplicity. (12th June 2019) - Crisp, Oliver D.
Abstract: Many recent treatments of divine simplicity have been highly critical of traditional accounts of the doctrine. Critics have challenged whether the doctrine is coherent and whether it can be squared with a robust theology of the triune God. Yet the theological tradition is largely persuaded that the doctrine of divine simplicity is not only coherent and true, but also that the doctrine of divine simplicity is needed for an account of the Trinity that does not fall into the trap of tritheism. In addition, both Roman Catholic and Protestant traditions include conciliar and confessional support for the doctrine, and allow for more than one way of accounting for the doctrine. This essay offers a constructive account that seeks to avoid some of the most significant concerns raised in the recent theological and philosophical literature. It depends in important respects upon work being done in analytic theology on the use of models in theology, adopted (with suitable amendments) from the philosophy of science. After giving some dogmatic context, three versions of divine simplicity are laid out. Then, a parsimonious version of the doctrine is set forth and considered as a potentially fruitful model, which may have theological utility. The essay ends with some remarks about the way in which this new model of the doctrine may have value in ecumenical theology.